Proceedings of the National Consultation Workshop on Food and Agriculture System Transformation in Nepal - Onta, Karuna; Pradhan, Mamata; Palikhe, Aruna; Maharjan, Nada; Mohan, Anisha (International Food Policy Research Institute, 2023)
The National Consultation Workshop on Food and Agriculture System Transformation in Nepal was held in Kathmandu, Nepal on May 18–19, 2023. The consultation was organized by International Food Policy Research Institute (IFPRI) and Institute for Integrated Development Studies (IIDS) with support from the United States Agency for International Development, Nepal (USAID/Nepal). This consultation was a part of generating insights / evidence for the United States Government’s (USG) Global Food Security Strategy-Refresh (GFSS-R) process. The US Government’s Global Food Security Strategy (GFSS) is an integrated whole-of-government approach that aims to end global hunger, poverty, and malnutrition through Feed the Future (FtF) initiatives. Several innovations in food and agriculture sectors have been successfully implemented in Nepal, being one of the oldest and most successful Feed the Future countries. However, more remains to be done to ensure food security in the nation. Farmers are still reliant on subsistence farming, leading to low agricultural productivity in the country. Rapid feminization in agriculture, owing to high outmigration and impact of climate change and natural disasters, has further burdened the poor, women, and marginalized groups in achieving food security. Additionally, the COVID-19 pandemic has had a significant negative impact on the country’s economy, thwarting the achievement of Sustainable Development Goals (SDGs). This National Consultation Workshop was designed with an objective to inform the GFSS-R 2022– 2026, with emphasis on i) equity and inclusion, ii) an ambitious approach to climate change, iii) countering the long-term impacts of COVID-19, iv) employing system thinking and working across food systems, and v) integration of conflict management, peace-building, and social cohesion. The Whole System in the Room (WSR) approach was applied to facilitate the workshop with 116 participants representing government, non-government organizations (NGOs), private sectors, and farmers from the federal, provincial, and local levels. Discussions during the consultation workshop were mostly centered on the proposed five themes: (i) Risk and Resilience Capacity, (ii) Food Systems Innovations, (iii) Markets and Trade, (iv) Food Systems Outputs and Outcomes, and (v) Food System Governance and Control. Additional sub-themes were identified to capture the status of each of the themes, and to address their gaps and constraints along with recommendations required to transform the food and agriculture system of Nepal. The participants have proposed specific prioritized recommendations from the list that was generated from the consultation. The summary of these prioritized recommendations for all five themes is given below.